The meanings of experiential-, collaborative-, and inquiry-based learning - Bae, Yena; Kwon, Danam (Edelweiss Applied Science and Technology, 2024)
Using interviews, this study explores the meanings of experiential-, collaborative-, and inquiry-based learning as perceived by professors and students. To achieve this goal, Focus Group Interviews were conducted with both professors and students. Experiential learning involves engaging in activities meaningful to students, including both direct and indirect experiences. Through students’ reflection, content is interpreted personally and transferred to other subjects or real-life situations. Collaborative learning is defined as two or more individuals gathering to solve a common problem and pooling their opinions to produce better outcomes than otherwise. Finally, inquiry-based learning involves acquiring knowledge and information through various methods and internalizing them intellectually, making them one’s own. Based on these findings, the study discusses the direction of changes in classroom teaching.